The Research of Underwater Acoustic Detection System for Small AUV - Wang Feng-Qi-Wu; Zhang Xin; Xing Xiao-Fei; Zhang Xiao-Ji (2015 Fifth International Conference on Instrumentation and Measurement, Computer, Communication and Control (IMCCC), 2015)
In order to solve the problem of the passive direction-finding and ranging in a sonar system of the small autonomous underwater vehicle (AUV), the optimized beam-forming (OBF) and the geometric positioning are proposed. Considering the strong target interference, the multiple thresholds are used for mitigating the interference, produced by the strength measurement and duration of signals, and then a beam-forming with receiving signals is done, and three of the biggest beams are interpolated to find the incident direction of signals. The distance between AUV and pingers are calculated by trigonometric function in geometric positioning algorithm, in the condition of keeping the AUV moving along mid-perpendicular between two pingers. The experiments were implemented in an anechoic tank and a swimming pool to evaluate the performance of the ranging and direction finding of the detection system, obtaining the detection mean square error within 2.5°. This work shows that the simultaneous measurement of the multiple underwater pinger' signals is feasible by using this underwater acoustic detection system.